Psychological Impact of the Gender Related Proverbs on the Life of Pashtun Woman: An Analysis in the Light of Foucault’s Concept of Power and Knowledge (Khairulummah, 2023)
Proverbs as a significant genre of the folklore and as a strong discourse has proved effective in the promotion and sustenance of stereotypical ideas about gender. The sustenance of stereotypical ideas about gender has added to the maintenance of the status quo. The maintenance of the status quo has promoted injustice, discrimination and inequality of gender which has affected the various aspects of woman’s life, including the psychological one. Linguistic sexism has been a tool which has been utilized in the proverbs of Pashto about woman and through denigration and belittlement, a sense of inferiority has been developed in her about her own worth, intelligence, potentials and capabilities. It would not be wrong to say that Pashto proverbs, which portray woman negatively have impacted her psyche about her negative self-image, which she has further transmitted to the women of coming generations. A mother will cultivate the same inferiority in her daughter and other younger which is a part of her training through the negative discourses. The current study is an effort in this regard. It will critically analyze the impact which gender biased proverbs have left on the psyche of woman and has added to the continuation of gendered culture and a social order based on imbalance. The critical analysis of proverbs about gender will be made in the light of Foucault’s concept of Power and Knowledge. The study is interpretive qualitative research, so, the tool of thematic analysis has been applied to it.